Positive plate and preparation method thereof, lithium ion battery and power utilization device

By designing a multi-layer film structure on the positive electrode sheet of the LFP battery, using conductive polymers and ternary positive electrode materials to block the migration of iron ions, the iron dissolution problem of lithium iron phosphate batteries at high temperatures is solved, and the cycle stability and service life of the battery are significantly improved.

CN119812194AActive Publication Date: 2025-04-11BYD CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411507730.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-11
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The lithium iron phosphate (LFP) battery has iron dissolution during circulation, resulting in the attenuation of the capacity of lithium-ion batteries, especially at high temperatures, resulting in the problem of battery circulation diving.

Method used

A positive electrode sheet including a positive electrode current collector and a multi-layer positive electrode film layer located on one side surface is used. The film layer consists of a first film layer (a phosphate positive electrode material containing iron element), a second film layer (conductive polymer) and a third film layer (ternary positive electrode material) that are laminated in sequence, and the third film layer may further include a ferrophilic metal oxide.

Benefits of technology

It significantly improves the cycle stability and service life of the battery under high temperature conditions, prevents iron ions from migrating to the negative electrode, slows down the increase in the internal resistance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812194A_ABST
    Figure CN119812194A_ABST
Patent Text Reader

Abstract

The invention relates to a positive plate and a preparation method thereof, a battery and an electric device. The positive plate comprises a positive current collector and a positive film layer positioned on at least one side surface of the positive current collector, the positive electrode film layer comprises a first film layer, a second film layer and a third film layer which are sequentially stacked on the positive electrode current collector; the first film layer comprises a phosphate positive electrode material containing an iron element; the second film layer comprises a conductive polymer; and the third film layer comprises a ternary positive electrode material. When the positive plate is used for the battery, the third film layer comprising the ternary positive electrode material can effectively block iron ions possibly generated by the phosphate positive electrode material containing the iron element in the first film layer in the charging and discharging process from migrating to a negative electrode, and the iron ions are prevented from being deposited on the negative electrode in the charging and discharging process of the battery. And the second film layer is arranged, so that more iron adsorption sites can be provided, the contact interface of the first film layer and the second film layer can be improved, and the overall electrochemical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a preparation method thereof, a lithium-ion battery and an electrical device. Background Art

[0002] In recent years, during the cycle of lithium iron phosphate (LFP) batteries, iron dissolution occurs in the positive electrode material, causing the capacity of lithium-ion batteries to decay. This phenomenon is more serious at high temperatures, and eventually leads to the problem of battery cycle diving. Therefore, the technology related to lithium iron phosphate batteries still needs to be improved. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a positive electrode sheet that significantly improves the cycle stability and service life of a battery under high temperature conditions.

[0004] In the first aspect of the present application, a positive electrode sheet is provided. According to an embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector; the positive electrode film layer includes a first film layer, a second film layer and a third film layer stacked in sequence on the positive electrode current collector; the first film layer includes a phosphate positive electrode material containing iron elements; the second film layer includes a conductive polymer; and the third film layer includes a ternary positive electrode material. The positive electrode sheet of the embodiment of the present application can significantly improve the cycle stability and service life of the battery under high temperature conditions, making it more suitable for application requirements in high temperature environments.

[0005] According to an embodiment of the present application, the positive electrode film layer further includes a fourth film layer, the fourth film layer is located on a surface of the third film layer away from the second film layer, and the fourth film layer includes a ferrophilic metal oxide.

[0006] According to an embodiment of the present application, the ferrophilic metal oxide includes at least one of iron oxide and titanium oxide.

[0007] According to an embodiment of the present application, the phosphate positive electrode material includes at least one of lithium iron phosphate and lithium iron manganese phosphate, preferably lithium iron phosphate;

[0008] The ternary positive electrode material includes at least one of a nickel-cobalt-manganese ternary positive electrode material and a nickel-cobalt-aluminum ternary positive electrode material, preferably a nickel-cobalt-manganese ternary positive electrode material.

[0009] According to an embodiment of the present application, the nickel-cobalt-manganese ternary positive electrode material has the following chemical composition:

[0010] Li(Ni x Co y Mn z )Q r O2

[0011] Wherein, x=0.3-1, y=0.01-0.5, z=0.01-0.5, r=0-0.1;

[0012] The Q element includes at least one of yttrium, zirconium, titanium, niobium, aluminum, magnesium, molybdenum, and niobium.

[0013] According to an embodiment of the present application, the ternary cathode material includes at least one of spherical nanoparticles, nanowires and nanosheets.

[0014] According to an embodiment of the present application, the D50 particle size of the spherical nanoparticles is 2-5 μm;

[0015] The aspect ratio of the nanowire is 2 to 5;

[0016] The aspect ratio of the nanosheet is 2-5.

[0017] According to an embodiment of the present application, the conductive polymer includes at least one of polyaniline and polypyrrole.

[0018] According to an embodiment of the present application, the second membrane layer also includes an iron ion adsorbent.

[0019] According to an embodiment of the present application, the iron ion adsorbent includes at least one of manganese-based ferrite (MnFe2O4), Fe3O4 magnetic nanomaterials, ethylenediaminetetraacetic acid (EDTA), and tannic acid (TA); and / or

[0020] Based on the total mass of the second membrane layer, the mass percentage of the iron ion adsorbent is 5% to 20%.

[0021] According to an embodiment of the present application, the thickness ratio of the first film layer, the second film layer and the third film layer is (0.5-1):(0.02-0.2):(0.02-0.3).

[0022] In a second aspect of the present application, a method for preparing the aforementioned positive electrode sheet is provided. According to an embodiment of the present application, the method comprises: coating a first slurry on at least one side surface of a positive electrode current collector and drying to form a first film layer; coating a second slurry on a surface of the first film layer away from the current collector and drying to form a second film layer; coating a third slurry on a surface of the second film layer away from the current collector to form a third film layer.

[0023] According to an embodiment of the present application, the method further includes coating a fourth slurry on a surface of the third film layer away from the current collector and drying the slurry to form a fourth film layer.

[0024] The third aspect of the present application provides a lithium-ion battery. According to an embodiment of the present application, the lithium-ion battery includes the positive electrode sheet described above. During the operation of the lithium-ion battery, the second film layer and the third film layer act as a barrier to intercept the iron ions generated in the first film layer and prevent them from being deposited on the negative electrode during the battery charging and discharging process, which not only improves the cycle stability of the battery under high temperature conditions, but also prolongs the service life of the battery, making it more suitable for application requirements in high temperature environments.

[0025] In a fourth aspect of the present application, an electric device is provided. According to an embodiment of the application, the electric device includes the lithium-ion battery described above. The electric device has all the features and advantages of the lithium-ion battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of a positive electrode sheet according to an embodiment of the present application.

[0027] Figure 2 It is a schematic structural diagram of a positive electrode sheet according to another embodiment of the present application.

[0028] Figure 3 It is a structural schematic diagram of a positive electrode sheet of another embodiment of the present application.

[0029] Figure 4 This is a SEM-EDS test result diagram of the iron deposition amount in the longitudinal section of the third film layer (ie, NCM layer) in the positive electrode sheet of the lithium-ion battery in Example 1 of the present application.

[0030] Figure 5 This is a test result diagram of TOF-SIMS characterizing the iron content on the surface of the positive electrode close to the diaphragm in the lithium-ion battery in Example 1 of the present application. DETAILED DESCRIPTION

[0031] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0032] This application is based on the inventor's discovery and understanding of the following facts and problems:

[0033] Iron dissolution is an important factor causing the capacity decay of LFP (lithium iron phosphate) batteries. The iron dissolution process and the series of reactions caused by its dissolution can be summarized into the following five steps:

[0034] 1) LiPF6 hydrolysis produces HF, LiF and POF3: Since LFP in the battery contains a small amount of water, the hydrolysis of electrolyte containing LiPF6 is widespread. In addition to the influence of water, electrolyte oxidation can also cause LiPF6 to hydrolyze and produce protons.

[0035] 2) The LFP surface is etched by HF: HF in the electrolyte reacts with the LFP surface. Specifically, 4 equivalents of HF can react with LiFePO4 to generate H2, LiF, H3PO4 and insoluble FeF3. In the presence of HF, LFP is etched, resulting in surface degradation. Subsequently, protons in the electrolyte and Fe 2+ / Fe 3+ An exchange occurs.

[0036] 3) Fe solvated in the electrolyte 2+ / Fe 3+ Migrate to the negative electrode. Solvated Fe 2+ / Fe 3+ It is formed by the dissolution of Fe compounds.

[0037] 4) Solvated Fe 2+ / Fe 3+ Once the Fe complex reaches the negative electrode, Fe 2+ / Fe 3+ May be reduced to Fe 0 And deposited on the negative electrode, and finally embedded in the SEI film.

[0038] 5) The impact of metal Fe deposition in the SEI film. Once Fe reaches the negative electrode, it will diffuse into the inner layer of the SEI film and may cause lithium precipitation. In addition, some studies have suggested that the dissolution of transition metals will lead to the degradation of the SEI film, and the organic components of the SEI film will decompose into inorganic lithium carbonate, thus leading to the continuous growth of the SEI.

[0039] The whole reaction process can be summarized as the following equation:

[0040] ① LiPF6 → LiF + PF5

[0041] ② PF5 + H2O → POF3 + 2HF

[0042] ③ POF3 + H2O → HPO2F2 + HF

[0043] ④ LiPF6 + 2H2O → LiPO2F2 + 4HF

[0044] ⑤ 4HF + LiFePO4 → FeF3 + 0.5H2 + LiF + H3PO4

[0045] The means of inhibiting the dissolution of iron from lithium iron phosphate (LiFePO4) usually involve modification of the electrolyte (electrolyte additives, etc.), surface treatment of electrode materials (carbon coating, etc.), optimization of battery structure (battery charge and discharge regime, control of state of charge (SOC), and battery temperature management, etc.), use of organic lithium salts (such as 3,4-dihydroxybenzonitrile dilithium, Li2DHBN), mechanochemical activation, closed-loop regeneration methods, etc. However, the various methods reported so far still have some disadvantages or problems that may arise: electrolyte additives may increase battery impedance and reduce the thermal stability of the electrolyte, carbon coating will increase production costs, organic lithium salts have harsh conditions for use, the complexity and cost of the production process increase, and specific technologies and equipment are required.

[0046] In order to overcome the above shortcomings to a certain extent, the present application relates to an improved positive electrode sheet, which can intercept Fe ions dissolved in the positive electrode material from migrating to the negative electrode for deposition.

[0047] In view of this, in the first aspect of the present application, a positive electrode sheet is provided. According to an embodiment of the application, referring to Figure 1 The positive electrode sheet includes a positive electrode current collector 10 and a positive electrode film layer 20 located on at least one side of the positive electrode current collector; the positive electrode film layer 20 includes a first film layer 21, a second film layer 22 and a third film layer 23 stacked in sequence on the positive electrode current collector 10; the first film layer 21 includes a phosphate positive electrode material containing iron elements; the second film layer 22 includes a conductive polymer; and the third film layer 23 includes a ternary positive electrode material. When the positive electrode sheet is used in a battery, during the charge and discharge cycle, the third film layer including the ternary positive electrode material not only has good electrochemical properties, but also can effectively block the migration of iron ions (Fe2+ / Fe3+) that may be generated by the phosphate positive electrode material containing iron elements in the first film layer during the charge and discharge process to the negative electrode; thus, the third film layer acts as a barrier to intercept the iron ions in the first film layer and prevent them from being deposited on the negative electrode during the charge and discharge process of the battery. The second film layer can provide more iron adsorption sites and improve the interception effect of iron ions. On the other hand, the conductive polymer has a certain flexibility and can improve the contact interface between the first film layer and the second film layer. On the other hand, the conductive polymer can also improve the conductivity of the electrode, optimize the overall electrochemical performance of the battery, and thus improve the overall electrochemical performance of the battery. Therefore, the positive electrode sheet of the embodiment of the present application can significantly improve the cycle stability and service life of the battery under high temperature conditions, making it more suitable for application requirements in high temperature environments.

[0048] Specifically, the third film layer can achieve a better effect of intercepting iron ions, mainly due to the dual action mechanism of the ternary positive electrode material. Specifically: the ternary positive electrode material has a certain water absorption, which enables it to act as a dehumidifier in the internal environment of the battery. In the manufacturing and use of lithium-ion batteries, the presence of water is inevitable, and the water in the electrolyte will react with the lithium salt in the electrolyte to generate corrosive substances such as hydrofluoric acid, which will damage the electrode material and accelerate the dissolution of iron ions in the phosphate positive electrode material. The water absorption of the ternary positive electrode material can effectively absorb trace moisture inside the battery, reduce the generation of corrosive substances, thereby slowing down the dissolution of iron ions in the phosphate positive electrode material and improving the chemical stability and cycle life of the battery.

[0049] In addition, there may be residual alkaline substances on the surface of the ternary cathode material, such as lithium hydroxide (LiOH) and lithium carbonate (Li2CO3). These alkaline substances form a stable chemical environment on the surface of the ternary cathode material, providing active sites for the deposition of iron ions. When the phosphate cathode material releases iron ions during the charge and discharge process, these sites can capture the iron ions and prevent them from further diffusing to the negative electrode. This capture effect not only reduces the deposition of iron ions at the negative electrode, but also reduces the increase in internal resistance of the battery caused by the deposition of iron ions, thereby maintaining the electrochemical performance of the battery.

[0050] Combining the above two points, the water absorption of the ternary positive electrode material and the presence of alkaline substances on the surface can effectively intercept iron ions, which not only improves the stability of the battery in high temperature environment, but also extends the battery life, providing strong technical support for the application of lithium-ion batteries under harsh conditions.

[0051] According to an embodiment of the present application, the positive electrode current collector may be a metal current collector or a composite current collector. For example, the metal current collector includes but is not limited to an aluminum foil current collector; the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base film. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material base film (such as a base film of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0052] According to an embodiment of the present application, the phosphate positive electrode material containing an iron element may include at least one of lithium iron phosphate and lithium iron manganese phosphate. As an example, the phosphate positive electrode material containing an iron element may be lithium iron phosphate.

[0053] According to an embodiment of the present application, in addition to the aforementioned iron-containing phosphate positive electrode material, the first film layer may also include a binder, a conductive agent, and optionally a functional additive. As an example, the binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and at least one of fluorine-containing acrylic resins; the conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0054] According to the embodiments of the application, the conductive polymer in the second film layer may include at least one of polyaniline and polypyrrole. Thus, the interface contact between the first film layer and the second film layer can be effectively improved, the overall electrochemical performance of the battery using the positive electrode sheet can be improved, and more iron ion adsorption sites can be provided to enhance the effect of intercepting iron ions.

[0055] According to an embodiment of the application, the second film layer also includes an iron ion adsorbent, thereby providing more iron ion adsorption sites, thereby effectively improving the effect of intercepting iron ions.

[0056] According to an embodiment of the application, the iron ion adsorbent may include at least one of manganese-based ferrite (MnFe2O4), Fe3O4 magnetic nanomaterials, ethylenediaminetetraacetic acid (EDTA), and tannic acid (TA), thereby achieving a better effect of adsorbing iron ions.

[0057] According to the embodiment of the application, based on the total mass of the second film layer, the mass percentage of the iron ion adsorbent is 5% to 20%, specifically 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc. Thus, while improving the effect of intercepting iron ions, it basically does not bring other negative effects.

[0058] According to an embodiment of the application, the ternary positive electrode material used in the third film layer includes at least one of a nickel-cobalt-manganese ternary positive electrode material and a nickel-cobalt-aluminum ternary positive electrode material. As an example, the ternary positive electrode material used in the third film layer is a nickel-cobalt-manganese ternary positive electrode material.

[0059] It can be understood that the nickel-cobalt-manganese ternary positive electrode material refers to lithium nickel-cobalt-manganese oxide, and the nickel-cobalt-aluminum ternary positive electrode material refers to lithium nickel-cobalt-aluminum oxide. In this article, the nickel-cobalt-manganese ternary positive electrode material and the nickel-cobalt-aluminum ternary positive electrode material are understood in a broad sense, which can include both unmodified intrinsic materials and modified materials that are doped and / or coated.

[0060] In addition, the nickel-cobalt-manganese ternary positive electrode material and the nickel-cobalt-aluminum ternary positive electrode material can generally be divided into low-nickel materials, medium-nickel materials, high-nickel materials and ultra-high-nickel materials according to the nickel content. The above-mentioned ternary positive electrode materials with different nickel contents can all be used in the third film layer. It can be understood that by accurately adjusting the molar ratio of nickel (Ni), cobalt (Co), manganese (Mn) or the molar ratio of nickel (Ni), cobalt (Co), and aluminum (Al) in the ternary positive electrode material, the electronic structure and chemical stability of the material can be optimized. For example, increasing the manganese content can improve the stability and safety of the material, while moderately increasing the nickel content helps to increase the capacity. Through this ratio adjustment, the third film layer can not only provide a stronger iron ion adsorption capacity, but also maintain the structural integrity during the charge and discharge process, thereby effectively inhibiting the dissolution of iron ions in the phosphate positive electrode material. As an example, in order to obtain a better use effect, a medium nickel ternary positive electrode material can be used in the third film layer.

[0061] In some embodiments, the nickel-cobalt-manganese ternary positive electrode material has the following chemical composition:

[0062] Li(Ni x Co y Mn z )Q r O2

[0063] Wherein, x=0.3-1, y=0.01-0.5, z=0.01-0.5, r=0-0.1;

[0064] The Q element includes at least one of yttrium, zirconium, titanium, niobium, aluminum, magnesium, molybdenum, and niobium.

[0065] As a specific example, the nickel-cobalt-manganese ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622).

[0066] Therefore, while having a better effect of intercepting iron ions, it is beneficial to improve the capacity and cycle stability of the battery using the positive electrode sheet.

[0067] According to the embodiments of the application, in order to obtain a better effect of intercepting iron ions, the morphology of the ternary cathode material particles can be adjusted. In some embodiments, the ternary cathode material includes at least one of spherical nanoparticles, nanowires and nanosheets. Thus, the specific surface area of ​​the ternary cathode material can be effectively increased. This high specific surface area nanostructure can not only provide more active sites for the adsorption of iron ions, but also shorten the diffusion path of lithium ions, thereby improving the charge and discharge rate and cycle stability of the battery.

[0068] According to the embodiments of the application, the D50 particle size of the spherical nanoparticles is 2 μm to 5 μm, such as 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.

[0069] In this application, D50 refers to the particle size corresponding to the volume cumulative particle size distribution percentage of a sample reaching 50%. Its physical meaning is that particles with a particle size larger than it account for 50% of the volume, and particles with a particle size smaller than it also account for 50% of the volume. D50 is also called the median diameter or median particle size. It can be detected by a laser particle size analyzer.

[0070] According to an embodiment of the application, the aspect ratio of the nanowire is 2 to 5, specifically 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.

[0071] In the present application, the aspect ratio of a nanowire refers to the ratio of the length of the nanowire to its diameter.

[0072] According to the embodiments of the application, the aspect ratio of the nanosheet is 2 to 5, specifically 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.

[0073] In the present application, the aspect ratio of a nanosheet refers to the ratio of the maximum distance between any two points on the plane contour line of the nanosheet to the minimum distance between any two points on the plane contour line of the nanosheet.

[0074] The ternary positive electrode material that meets the above dimensions has a larger specific surface area and is easier to capture iron ions.

[0075] According to the embodiments of the application, refer to Figure 3 The positive electrode film layer 20 further includes a fourth film layer 24, which is located on the surface of the third film layer 23 away from the second film layer 22, and includes a ferrophilic metal oxide. Thus, the adsorption sites of iron ions can be effectively increased, which can not only improve the capture efficiency of the third film layer for iron ions, but also form a more stable SEI film during the battery charging and discharging process, slow down the decomposition of the electrolyte, and extend the service life of the battery.

[0076] According to an embodiment of the application, the ferrophilic metal oxide includes at least one of iron oxide and titanium oxide, thereby achieving a better iron ion adsorption effect.

[0077] According to an embodiment of the application, the thickness ratio of the first film layer, the second film layer and the third film layer can be (0.5-1):(0.02-0.2):(0.02-0.3). Thus, the area close to the first film layer can have a higher iron ion adsorption capacity and better chemical stability.

[0078] In a second aspect of the present application, a method for preparing the aforementioned positive electrode sheet is provided. According to an embodiment of the application, the method comprises:

[0079] S1: coating a first slurry on at least one side of a positive electrode current collector and drying the slurry to form a first film layer.

[0080] Specifically, in this step, the raw material of the first film layer can be prepared into a first slurry, and then the first slurry is coated on at least one side surface of the positive electrode current collector, and then dried to form the first film layer.

[0081] Specifically, the specific operations of coating the slurry and drying are not particularly limited in this application and can be flexibly selected according to actual needs. For example, they can be performed according to conventional techniques.

[0082] In some embodiments, the raw materials of the first film layer include a phosphate positive electrode material containing iron, a binder, a conductive agent, and a first solvent. The phosphate positive electrode material containing iron, the binder, and the conductive agent can be consistent with the above description, and will not be repeated here. The first solvent includes but is not limited to N-methylpyrrolidone (NMP) and the like.

[0083] S2: coating a second slurry on a surface of the first film layer away from the current collector and drying the slurry to form a second film layer.

[0084] Specifically, in this step, the raw material of the second film layer can be prepared into a second slurry, and then the second slurry is coated on the surface of the first film layer away from the positive electrode current collector, and then dried to form the second film layer.

[0085] Specifically, the specific operations of coating the slurry and drying are not particularly limited in this application and can be flexibly selected according to actual needs. For example, they can be performed according to conventional techniques.

[0086] In some embodiments, the raw material of the second film layer includes a conductive polymer and a second solvent. The conductive polymer may be consistent with the above description, and will not be described in detail here. The second solvent includes but is not limited to NMP.

[0087] In some embodiments, the raw materials of the second film layer include a conductive polymer, an iron ion adsorbent, and a second solvent. The iron ion adsorbent may be consistent with the above description, and will not be described in detail here.

[0088] S3: coating a third slurry on a surface of the second film layer away from the current collector to form a third film layer.

[0089] Specifically, in this step, the raw material of the third film layer can be prepared into a third slurry, and then the third slurry is coated on the surface of the second film layer away from the positive electrode current collector, and then dried to form the third film layer.

[0090] Specifically, the specific operations of coating the slurry and drying are not particularly limited in this application and can be flexibly selected according to actual needs. For example, they can be performed according to conventional techniques.

[0091] In some embodiments, the raw materials of the third film layer include a ternary positive electrode material, a binder, a conductive agent, and a third solvent. The ternary positive electrode material, the binder, and the conductive agent may be consistent with the above description, and will not be repeated here. The third solvent includes but is not limited to N-methylpyrrolidone (NMP) and the like.

[0092] According to an embodiment of the application, the method further includes coating a fourth slurry on a surface of the third film layer away from the current collector and drying the slurry to form a fourth film layer.

[0093] Specifically, in this step, the raw material of the fourth film layer can be prepared into a fourth slurry, and then the fourth slurry is coated on the surface of the third film layer away from the positive electrode current collector, and then dried to form the fourth film layer.

[0094] Specifically, the specific operations of coating the slurry and drying are not particularly limited in this application and can be flexibly selected according to actual needs. For example, they can be performed according to conventional techniques.

[0095] In some embodiments, the raw materials of the fourth film layer include a ferrophilic metal oxide, a film-forming aid and a third solvent. The ferrophilic metal oxide may be consistent with the above description and will not be described in detail here. The film-forming aid includes but is not limited to PVDF, etc., and the third solvent includes but is not limited to NMP, etc.

[0096] In a third aspect of the present application, a lithium-ion battery is provided. According to an embodiment of the application, the lithium-ion battery includes the positive electrode sheet described above. During operation of the lithium-ion battery, the second film layer and the third film layer act as a barrier to intercept the iron ions generated in the first film layer and prevent them from being deposited on the negative electrode during the battery charging and discharging process, which not only improves the cycle stability of the battery under high temperature conditions, but also prolongs the service life of the battery, making it more suitable for application requirements in high temperature environments.

[0097] It can be understood that there is no particular limitation on the specific type of the battery, including but not limited to lithium-ion batteries, sodium-ion batteries, etc., and the battery can be a square shell battery, a soft pack battery, a cylindrical battery, etc., and can be in different forms such as a battery cell, a battery module, a battery pack, etc.

[0098] It is also understood that, in addition to the aforementioned positive electrode sheet, the battery may also include other necessary structures and components of conventional batteries. For example, it may include an outer package, and an electrode assembly and an electrolyte contained in the outer package, and the electrode assembly may include the aforementioned positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet.

[0099] As an example, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer located on at least one side of the negative electrode current collector, and the negative electrode film layer generally contains a negative electrode active material, a conductive agent and a binder. The electrolyte generally includes an electrolyte salt and a solvent. The above-mentioned negative electrode active material, binder, conductive agent, current collector, electrolyte salt and solvent can be selected with reference to conventional technology, and this application does not make any special restrictions.

[0100] In a fourth aspect of the present application, an electric device is provided. According to an embodiment of the application, the electric device includes the lithium-ion battery described above. The electric device has all the features and advantages of the lithium-ion battery described above, which will not be described one by one here.

[0101] According to an embodiment of the present application, the power-consuming device may include a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc., but is not limited thereto. The battery may be used as a power source for the power-consuming device, or may be used as an energy storage unit for the power-consuming device.

[0102] It can be understood that in addition to the lithium-ion battery mentioned above, the electrical device can also include the necessary structures and components of conventional electrical devices. Taking electric vehicles as an example, they can include the necessary structures and components such as the body, windows, chassis, engine, seats, tires, etc., which will not be repeated here.

[0103] The embodiments of the present application are described in detail below.

[0104] The lithium ion batteries of the following Examples 1 to 9 and Comparative Example 1 were prepared in the following manner, and the specific parameter differences are shown in Table 1:

[0105] (1) Preparation of positive electrode sheet of comparative example

[0106] The positive electrode active material LFP, the conductive agent acetylene black and carbon nanotubes CNT, and the binder PVDF are mixed in a mass ratio of 97.5:0.5:2, and the solvent NMP is added and stirred into a uniform slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after oven drying, it is rolled, slit, and die-cut into positive electrode sheets.

[0107] (2) Preparation of positive electrode sheet of the embodiment

[0108] The positive electrode active material LFP, the conductive agent acetylene black and the carbon nanotube CNT, and the binder PVDF are mixed in a mass ratio of 97.5:0.5:2, and the solvent NMP is added to stir into a uniform slurry, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil to form a first film layer;

[0109] The conductive polymer polyaniline and the solvent NMP are mixed and stirred into a uniform slurry, and the slurry is evenly coated on the surface of the first film layer away from the current collector to form a second film layer;

[0110] The positive electrode active material NCM622 (D50 particle size is 4 μm), the conductive agent acetylene black and carbon nanotubes CNT, and the binder PVDF are mixed in a mass ratio of 97.5:0.5:2, and the solvent NMP is added and stirred into a uniform slurry. The positive electrode slurry is evenly coated on the surface of the second film layer away from the current collector, and after oven drying, it is rolled, slit, and die-cut into positive electrode sheets.

[0111] (3) Preparation of negative electrode sheet

[0112] The negative electrode active material graphite, conductive agent, binder SBR, and thickener CMC are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to stir into a uniform slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, and after drying in an oven, it is roll-pressed to obtain a negative electrode sheet.

[0113] (4) Preparation of electrolyte

[0114] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1 and vinylene carbonate VC is added to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L.

[0115] (5) Preparation of isolation membrane

[0116] A polyethylene film coated with ceramic glue on both sides is selected as the isolation film.

[0117] (6) Preparation of lithium-ion batteries

[0118] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to isolate the positive and negative electrodes. Then, the electrode core is obtained by stacking the sheets, and the electrode core is placed in an outer packaging shell, and the electrolyte is injected. After packaging, standing, formation, capacity division and other processes, a lithium-ion battery is obtained.

[0119] Example 10

[0120] The preparation method is the same as above, except that the conductive polymer polyaniline, the iron ion adsorbent Fe3O4 and the solvent NMP are mixed and stirred into a uniform slurry, which is evenly coated on the surface of the first film layer away from the current collector to form a second film layer, wherein the mass percentage of the iron ion adsorbent Fe3O4 is 10% based on the total mass of the second film layer.

[0121] Embodiment 11

[0122] The preparation method is the same as above, with the difference being: Fe2O3 and film-forming aid PVDF are mixed in a mass ratio of 95:5, solvent NMP is added, stirred into a uniform slurry, and evenly coated on the surface of the third film layer away from the current collector, and after oven drying, it is rolled, slit, and die-cut into positive electrode sheets.

[0123] Example 12

[0124] The preparation method is the same as above, except that the NCM622 particles are nanowires (aspect ratio of 4).

[0125] Embodiment 13

[0126] The preparation method is the same as above, except that the NCM622 particles are nanosheets (aspect ratio of 4).

[0127] Embodiment 14

[0128] The preparation method is the same as above, the difference is: using doped NCM: LiNi 0.6 Co 0.15 Mn 0.2 Zr 0.05 O2.

[0129] Embodiment 15

[0130] The preparation method is the same as above, the difference is: using low nickel NCM: LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0131] Example 16

[0132] The preparation method is the same as above, the difference is: using high nickel NCM: LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0133] Embodiment 17

[0134] The preparation method is the same as above, the difference is: using NCA: LiNi 0.8 Co 0.15 Al 0.05 O2.

[0135] Table 1

[0136]

[0137]

[0138] Note: The content of ternary positive electrode material refers to the mass percentage of the ternary positive electrode material in the third film layer based on the total mass of the positive electrode film layer; the initial VC residue refers to the VC content in the electrolyte when the electrolyte is prepared.

[0139] Battery performance test

[0140] The examples were tested by SEM-EDS, TOF-SIMS, 45°C cycle capacity retention, VC consumption, and iron dissolution.

[0141] The test method is as follows:

[0142] 1) SEM-EDS test: The disassembled positive electrode sheet was cleaned with anhydrous DMC (dimethyl carbonate). After the solvent evaporated, a 1 cm × 1 cm electrode sheet was taken. The positive electrode sheet was sputtered by argon ions to obtain a flat cross section. The sample was pasted on the sample stage with conductive glue to ensure the conductive path. During the sample preparation process, the sample should be prevented from being contaminated and damaged, and the original structure and morphology of the observation surface should be maintained. The conditions of each step were controlled to ensure the sample quality. The SEM-EDS information of the cross section at different magnifications of the selected area was obtained to obtain the distribution of the Fe element content. The test results of Example 1 are shown in Figure 4 .from Figure 4 It can be seen that after cycling, the iron ion content in the NCM layer increases, and the closer to the LFP layer, the higher the content, indicating that iron is intercepted by the NCM layer after escaping from the LFP layer.

[0143] 2) TOF-SIMS test: The disassembled positive electrode sheet was cleaned with anhydrous DMC. After the solvent evaporated, a 1 cm×1 cm electrode sheet was taken to analyze the element distribution on the surface of the positive electrode sheet. The Fe element distribution test results in Example 1 are shown in Figure 5 , Figure 5 The left side shows the test results before the cycle, and the right side shows the test results after the cycle. Figure 5 It can be seen that there is no obvious increase in the iron ion content on the surface of the NCM layer (close to the diaphragm side) after 300 cycles, indicating that the iron is intercepted by the NCM layer after escaping from the LFP layer.

[0144] 3) Perform a 45°C cycle capacity retention test on the battery. The test process is as follows:

[0145] Test procedure: Ambient temperature: 45℃, start the test after 5h of storage; perform 45℃ cycle test according to the following procedure:

[0146] ①Charging: 1C constant current charging to 3.8V, leave for 10 minutes;

[0147] ②Discharge: 1C constant current to 2.0V, leave for 10min.

[0148] ③Loop 300 times.

[0149] 4) Perform VC residual test on the battery. The test process is as follows:

[0150] ① The battery is discharged to 2.0V at room temperature with a current of 1 / 3C;

[0151] ② In the glove box, add ethyl propionate (EP) to the battery in a quantitative manner according to the ratio of EP to battery liquid injection = 1:1, and seal the battery with a sealing machine;

[0152] ③ Shake at 75Hz for three days, then use ultrasonic cleaner for 30min to fully mix EP with the electrolyte in the battery;

[0153] ④ Take the mixed solution and measure GC-MS to obtain the peak area of ​​each component. The concentration of each component in the mixed solution can be calculated based on the standard curve;

[0154] ⑤ Use the known EP addition amount to quantitatively infer the content of each component of the electrolyte.

[0155] 5) Negative electrode Fe content test: The disassembled negative electrode is cleaned with anhydrous DMC. After the solvent evaporates, the negative electrode dressing is scraped off the electrode and transferred into a sample tube for ICP test.

[0156] Table 2

[0157]

[0158]

[0159] Note: Formation VC residue refers to the VC content in the electrolyte after battery formation, formation Fe content refers to the Fe content in the negative electrode after battery formation, 300-cycle VC residue refers to the VC content in the electrolyte after the battery is cycled 300 times, and 300-cycle Fe content refers to the Fe content in the negative electrode after the battery is cycled 300 times.

[0160] The above tests show that the battery coated with the NCM layer shows an extended cycle life, and the inflection point of performance degradation is significantly delayed compared with the control example. This result shows that the introduction of the NCM layer effectively improves the cycle stability of the battery.

[0161] Furthermore, by disassembling and analyzing the chemical composition of the cycled batteries, it was found that in the battery of the single LFP system of Comparative Example 1, after the VC additive was consumed, the amount of iron ions dissolved increased significantly, resulting in an inflection point in the battery performance. In the battery of the embodiment in which the positive electrode sheet was coated with the second film layer and the third film layer, even after the VC additive was consumed, the amount of iron ions dissolved on the negative electrode side was still within the error range and was almost negligible.

[0162] Based on the above experimental data and analysis results, it can be concluded that the coating of the second and third film layers provides additional deposition sites for iron ions, thereby inhibiting the dissolution of iron ions during the battery charge and discharge process. This inhibitory effect slows down the decomposition of the electrolyte and the degradation of the SEI film, maintains a stable chemical environment inside the battery, and significantly improves the battery's cycle performance. In addition, the experimental results also show that the introduction of the second and third film layers does not have a negative impact on the initial capacity or discharge platform of the battery.

[0163] In summary, the present invention successfully achieved effective control of the dissolution behavior of iron ions by coating the second film layer and the third film layer on the surface of the LFP electrode, significantly improving the cycle stability and service life of the battery. This discovery provides a new technical approach for the design and optimization of lithium-ion batteries, and has important practical application value and market potential.

[0164] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0165] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0166] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode film layer located on at least one side surface of the positive electrode current collector; The positive electrode film layer comprises a first film layer, a second film layer and a third film layer sequentially stacked on the positive electrode current collector; The first film layer includes a phosphate positive electrode material containing iron elements; The second film layer includes a conductive polymer; The third film layer includes a ternary positive electrode material.

2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode film layer further includes a fourth film layer, the fourth film layer is located on the surface of the third film layer away from the second film layer, and the fourth film layer includes a ferrophilic metal oxide.

3. The positive electrode sheet according to claim 2, characterized in that: The ferrophilic metal oxide includes at least one of iron oxide and titanium oxide.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The phosphate positive electrode material comprises at least one of lithium iron phosphate and lithium iron manganese phosphate, preferably lithium iron phosphate; and / or The ternary positive electrode material includes at least one of a nickel-cobalt-manganese ternary positive electrode material and a nickel-cobalt-aluminum ternary positive electrode material, preferably a nickel-cobalt-manganese ternary positive electrode material.

5. The positive electrode sheet according to claim 4, characterized in that: The nickel-cobalt-manganese ternary positive electrode material has the following chemical composition: Li (Ni x Co y Mr z )Q r O2 Wherein, x=0.3-1, y=0.01-0.5, z=0.01-0.5, r=0-0.1; The Q element includes at least one of yttrium, zirconium, titanium, niobium, aluminum, magnesium, molybdenum, and niobium.

6. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The ternary cathode material includes at least one of spherical nanoparticles, nanowires and nanosheets.

7. The positive electrode sheet according to claim 6, characterized in that: The D50 particle size of the spherical nanoparticles is 2 μm to 5 μm; and / or The aspect ratio of the nanowire is 2 to 5; and / or The aspect ratio of the nanosheet is 2-5.

8. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The conductive polymer includes at least one of polyaniline and polypyrrole.

9. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The second membrane layer also includes an iron ion adsorbent.

10. The positive electrode sheet according to claim 9, characterized in that: The iron ion adsorbent comprises at least one of manganese-based ferrite, Fe3O4 magnetic nanomaterials, ethylenediaminetetraacetic acid, and tannic acid; and / or Based on the total mass of the second membrane layer, the mass percentage of the iron ion adsorbent is 5% to 20%.

11. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The thickness ratio of the first film layer, the second film layer and the third film layer is (0.5-1):(0.02-0.2):(0.02-0.3).

12. A method for preparing the positive electrode sheet according to any one of claims 1 to 11, characterized in that: include: Coating a first slurry on at least one side of the positive electrode current collector and drying the slurry to form a first film layer; Coating a second slurry on a surface of the first film layer away from the current collector and drying the slurry to form a second film layer; A third slurry is coated on a surface of the second film layer away from the current collector to form a third film layer.

13. The method according to claim 12, characterized in that The method further includes coating a fourth slurry on a surface of the third film layer away from the current collector and drying the slurry to form a fourth film layer.

14. A lithium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 11.

15. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 14.

Citation Information

Patent Citations

  • Mixed positive material of lithium-ion power battery

    CN103618084A

  • Battery cathode and preparation method thereof

    CN109461922A

  • Preparation method of power type lithium ion battery

    CN111276757A

  • Electrochemical device and electronic device

    CN113422000A

  • Positive pole piece with three-layer structure as well as preparation method and application of positive pole piece

    CN115472767A